Revitalization of Pico-Hydro Pelton Turbines for Operation at Low Head: An Experimental Study and Efficiency Analysis - Andi Saidah; Yudi Albari (CV Edujavare Publishing, 2026)
The transition to clean energy in Indonesia by 2025 is a key issue in national energy policy, with a target renewable energy mix ranging from 17–20%, adjusted from the previous target of 23%. One energy source with development potential is the pico-hydro power generation system with a capacity below 5 kW, particularly for remote areas not yet connected to the main power grid. This study aims to design and experimentally test a modified Pelton turbine capable of operating effectively under low-head conditions (<10 m) with a relatively constant flow rate. The research variables include variations in water flow rate between 0.5–2.0 L/s, head in the range of 2–8 m, and changes in generator load. Turbine design development was carried out by modifying the nozzle, varying the runner diameter between 100–250 mm, adjusting the water jet angle, and altering the number of blades on the runner to achieve optimal performance. This study is expected to yield performance data on the hydraulic and mechanical efficiencies of the Pelton turbine under low-head conditions, with a target efficiency of over 50% and an output power of up to 5 kW. The findings of this study are expected to contribute scientifically to the development of small-scale water turbine technology and support the utilization of renewable energy for rural electrification, in line with Sustainable Development Goals (SDGs) 7 and 13.